Synergistic Effects of Andrographolide on DNA Damage Repair Mechanism and Apoptosis in Breast Cancer Cells - Venkateshwari Ananthapur,; Pushpanjali Pendyala,; Prathiba Nallari, (International Journal of Phytomedicine, 2018)
Breast cancer is the second leading cause of cancer deaths in women. Several drugs including cisplatin and carboplatin have shown tremendous effectivity in reducing cancer; however development of drug resistance by breast cancer cells to overcome cytotoxic insults and recurrence of the disease is a major concern at the moment. Andrographolide is a diterpenoid with a potent anti-inflammatory and anti tumor activity and it’s usage in combination therapy would be ideal as it is proven for it’s apoptotic capability in varied number of cells. Antiproliferative and apoptotic activity of andrographolide in triple negative MDA-MB-231 cells was evaluated by clonogenic assay and flow cytometric analysis. Expression and phosphorylation of proteins were evaluated by immunoblotting. Our results revealed dose-dependent cytotoxic effects of andrographolide in MDA-MB-231 cells with and without carboplatin. It resulted in G2/M arrest of cells when treated alone, and further enhanced upon treatment in combination with carboplatin. Andrographolide alone and in combination with carboplatin enhanced apoptotic cells in early, mid and late stages and increased expression of DNA damage repair response proteins including FANCJ, FANCD2, RAD51, pRPA32 and p53. The present study strongly suggests that andrographolide inhibits breast cancer cell proliferation by apoptosis mediated through cell cycle arrest and up regulation of DNA damage repair response gene expression and shows synergistic effects upon usage in combination with carboplatin.